Crisis and Reconstruction of Teachers’ Professional Identity: The Case of Secondary School Teachers in Spain - Bolívar, Antonio; Domingo, Jesús; Pérez-García, Purificación (The open sports sciences journal, 2014)
While the teachers’ identity crisis is a recurring dilemma, it has acquired its own set of characteristics at the end of modernity. In addition, there are characteristics specific to secondary school teachers in Spain. Therefore, this topic must be placed within the broader framework of the modernity crisis and the academic community. From a narrative-biographical perspective, identities are constructed within a socialization process, like a story. This article describes the design of a study on the professional identity crisis of secondary school teachers in Spain. The study sequentially combines different individual interviews and focus groups. The research can be considered a collective case study , a multiple case study (individual interviews), and a greater collective study (focus groups). Finally, this article presents some of the study’s main conclusions. Identity is crucial to how teachers construct the nature of their work on a daily basis (motivation, satisfaction and competence). Therefore, and given the current crisis, it is necessary to evaluate alternative discourses that can lead to better school systems and a reconstruction of teachers’ identity in the academic community.